Musa beccarii (Musaceae) varieties in Sabah, Northern Borneo - Markku Häkkinen; Monica Suleiman; Johnny Gisil Gisil (The Japanese Society for Plant Systematics, 2005)
Musa beccarii Simmonds var. 'beccarii' is re-described based on extensive field studies in the eastern part of Sabah, Malaysia. Then a new variety of wild banana, M. beccarii Simmonds var. 'hottana' Häkkinen, is described and illustrated. This extremely rare new variety was only found in one area at the lower Kinanbatangan River, eastern part of Sabah. It is also considered that M. pigmaea, M. Hott nom. nud. from East Kalimantan, Indonesia, might be the synonym or a closely related variety to the new variety.